EXPLORATION OF ETHNOMATHEMATICS IN THE GRAND MOSQUE OF KERATON KASUNANAN SURAKARTA AS A MATHEMATICS LEARNING MEDIA - Mubarak, Muhamad Ilham; Setyaningsih, Nining (Jurnal Pendidikan Matematika dan IPA, 2025)
This study aims to describe the application of ethnomathematics in the architectural elements of the Grand Mosque of Keraton Kasunanan Surakarta, particularly in geometry topics, and to explore its use as a meaningful mathematics learning medium. Through a qualitative method with an ethnographic approach, this research explores the application of concepts such as flat shapes, solid shapes, and geometric transformations in architectural elements such as columns, towers, roofs, and mosque ornaments. The results of the study indicate that the architecture of the Grand Mosque of Surakarta is not only rich in historical and cultural values but also reflects relevant geometric concepts. This research identifies ethnomathematics in the Grand Mosque of Keraton Kasunanan Surakarta in the form of (1) Flat shape concepts, (2) Geometric transformation concepts, (3) Solid shape concepts; and the mathematical values contained in the Grand Mosque of Keraton Kasunanan Surakarta, including (1) Practical value and utility value, (2) Discipline value, (3) Cultural value. The study emphasizes that the integration of ethnomathematics in the curriculum can assist students in understanding mathematical concepts within the context of local culture, making them more relevant and meaningful. Thus, ethnomathematics at the Grand Mosque of Keraton Kasunanan Surakarta has the potential to offer a mathematics learning perspective that connects academic aspects with cultural and aesthetic values.